Implementation of the E-Kinerja System to Improve Public Service Quality at Bukit Biru Village - Robiyandi Robiyandi; Saipul Saipul; Kus Indarto (Poltanesa, 2025)
In response to the growing need for effective governance and public service delivery, this study investigates the implementation of the E-Kinerja system at Bukit Biru Village, Tenggarong District, Kutai Kartanegara Regency. The system was introduced as part of the Regulation of the Minister for Administrative and Bureaucratic Reform of the Republic of Indonesia No. 6/2022, which mandates the use of electronic performance management systems within government institutions. The purpose of this regulation is to improve the efficiency, transparency, and accountability of public servants, thereby enhancing the quality of public services. The E-Kinerja system, designed to manage, monitor, and evaluate employee performance more effectively, is expected to streamline public service delivery and align it with organizational goals. This research employs a qualitative descriptive approach to explore the implementation process and its impact on public service quality in the Bukit Biru Village government office. The study includes interviews with government officials, staff observations, and document analysis of the E-Kinerja system's application. The findings suggest that while the system has shown potential in improving the tracking and evaluation of employee performance, its implementation has faced several challenges. These challenges include limited training opportunities, a lack of thorough understanding among employees regarding the benefits and features of the system, and inconsistent participation in using the E-Kinerja platform. Furthermore, the study reveals that some critical factors support the implementation process, including the leadership's commitment to adopting new technologies, the integration of the system with existing human resource management practices, and the alignment of the system’s objectives with the goals of the public sector. However, despite these positives, the study identifies several barriers that undermine the effectiveness of the system, such as insufficient communication regarding the importance of employee engagement, the complexity of the platform, and technical limitations such as inconsistent internet access. This study highlights the importance of providing continuous training and ensuring that all employees understand the advantages of using the E-Kinerja system for both their individual development and the overall improvement of public services. Additionally, a robust communication strategy is crucial to ensuring employee buy-in and effective implementation. The research concludes by suggesting several policy recommendations aimed at optimizing the E-Kinerja system, such as enhancing staff involvement in the decision-making process, improving access to resources, and reinforcing the commitment to public service quality through better managerial support. This paper contributes to the growing body of literature on public administration and electronic government systems, offering valuable insights into the implementation challenges and opportunities that come with digitizing government performance management. It also provides a case study for other governmental bodies in Indonesia and beyond that aim to implement similar E-Kinerja systems to strengthen public sector governance and improve service delivery.